I want it that way - Backstreet Boys; Zomba Recording Corporation (Los Angeles, California : Zomba Recording Corporation, 1999)
Contains three tracks taken from Milennium album.
CD 1 : I Want It That Way / (3:34) -- My Heart Stays With You / (3:37) -- I'll Be There For You / (4:43).
Koleksi Khas Wiramanja.
Title from disc label.